THE IMPORTANCE OF INTERCULTURAL COMPETENCE IN THE CONTEXT OF ACADEMIC MOBILITY. TRAINING NEEDS - Florentina-Lavinia MATEI (Association of Social and Educational Innovation, 2021)
In recent decades, intercultural competence has become increasingly appreciated by students doing international mobility internships, being seen as a response to the challenges they may encounter during such an internship. The study aims to identify learners' perceptions of intercultural competence, as well as their possible training needs in this competence, before their participation in an international mobility internship, through the Erasmus Plus program. The study data were collected by applying a questionnaire, which was administered before the students' participation in the mobility internship. The study involved 130 students, 62 male and 68 female, aged between 19 and 50 years. The data analysis indicates that students perceive intercultural competence as important for completing an internship in international academic mobility. This competence, they believe, would help them to know and understand better, but also to respect the norms, traditions and customs of the host culture. At the same time, this competence would help students in both professional and personal development. The results can be used to create a training program for students who will participate in mobility internships.